2017
DOI: 10.1111/vde.12420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intraepidermal nerve fibres in the skin of normal and atopic dogs

Abstract: IENFs are detected more commonly in canine AD than in normal haired skin; these results are comparable to those seen for human AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Additionally, some mediators released by keratinocytes such as TSLP and periostin [ 78 ] are able to directly elicit itch by acting on sensory nerves [ 79 ]. This is particularly relevant in chronic disease [ 80 ] in which increased density of nerve fibers [ 81 ] and enhanced peripheral sensitization play a role and can contribute to a decreased response to antipruritic therapy. Thus, keratinocytes are far from being a physical inert barrier, and they are an integral part of a cross talk with the nervous system and the immune cells.…”
Section: Dogsmentioning
confidence: 99%
“…Additionally, some mediators released by keratinocytes such as TSLP and periostin [ 78 ] are able to directly elicit itch by acting on sensory nerves [ 79 ]. This is particularly relevant in chronic disease [ 80 ] in which increased density of nerve fibers [ 81 ] and enhanced peripheral sensitization play a role and can contribute to a decreased response to antipruritic therapy. Thus, keratinocytes are far from being a physical inert barrier, and they are an integral part of a cross talk with the nervous system and the immune cells.…”
Section: Dogsmentioning
confidence: 99%
“…The cells of the epidermis (keratinocytes) and the innate immune system play a critical role in AD, as shown not only in humans and rodents ( 5 ), but also in dogs ( 6 ). It has been shown that the skin of dogs with AD produces potent inflammatory mediators ( 7 ) and neurotrophins ( 8 ), which may be related to the hyperinnervation of the AD lesions ( 9 ). Pruritus, one of the most severe clinical signs of AD, is caused by a complex interface between pruritogenic molecules, keratinocytes, immunocytes, cutaneous nerve fibers, and the peripheral and central nervous systems ( 10 ).…”
Section: Introductionmentioning
confidence: 99%